Recognizing encephalopathy in immune checkpoint inhibitor therapy: A single‐center experience. (3rd March 2021) - Wei, Danmeng; Zhou, Daniel J.; Datta, Proleta; Taraschenko, Olga
Abstract: Background: In this pilot study, we examined the characteristics of patients with and without central nervous system (CNS) malignancies who developed immune checkpoint inhibitor (ICI)‐induced encephalopathy. Methods: We identified adult patients treated with ICIs between 1 January 2013 and 9 May 2018 at our tertiary care center who developed encephalopathy within 30 days of the last dose of ICI without other explained causes. Demographic and clinical features were compared between patients with primary and metastatic malignant CNS tumors and those without. Results: Of the 480 patients treated with ICIs, 14 (2.9%) developed encephalopathy induced by nivolumab (8), pembrolizumab (4), and combined ipilimumab‐nivolumab (2). Median age was 64.5 years. Patients with CNS malignancies tolerated more treatment cycles and developed encephalopathy later than patients without CNS lesions (20 and 32 days, respectively, p = 0.04) following ICI initiation. Four of seven patients with CNS tumors developed new contrast‐enhancing lesions on brain imaging despite having no changes on imaging for a median of 61 (30–545) days. Electroencephalogram (EEG) revealed features of generalized dysfunction in patients in both cohorts. Two patients without and three with CNS malignancies were treated with steroids. Two thirds of patients without and 29% of those with CNS malignancies expired during ICI therapy or shortly thereafter. Conclusions: Lack of the uniform evaluation limits the definitive conclusion of the cause of encephalopathy in some patients but reflects the standard of care at the time of their assessment. ICI‐associated neurotoxicity presenting with encephalopathy is an ominous complication of ICI therapy, especially if left untreated. Prompt recognition and involvement of multidisciplinary care, including neurologists, would facilitate timely administration of recommended therapies. Abstract : Patients receiving treatment with immune checkpoint inhibitors, a novel class of anticancer medications, can develop confusion, decreased responsiveness, headaches, and seizures that, if left untreated, can be fatal. We assessed the frequency of these neurological side effects in patients with and without tumors of the brain and compared their management at our institution. We found that the evaluation of patients in both groups was often incomplete. We also determined that the majority of patients were not treated according to the recommended guidelines and most of these patients were deceased shortly following their admission to the hospital. We concluded that the complications of immune checkpoint inhibitor therapy are not readily recognized by practitioners. We summarized the existing recommendations for the evaluation and treatment of these patients and proposed that neurologists be included in multidisciplinary efforts to treat these patients.